Analisis Kawasan Permukiman Rawan Bencanalongsor Berbasis Mitigasi Bencana Di Ibu Kota Kec. Sinjai Tengah Kab. Sinjai: ( Studi Kasus Kelurahan Samaenre) - Laode Miftah Fauzan Manan; Agus Salim; Ilham Yahya (Journal of Urban Planning Studies, 2021)
The purpose of this study was to determine the Analysis of Landslide-Prone Residential Areas Based on Disaster Mitigation in the Capital City, Sinjai Tengah District, Sinjai Regency. The variables used consisted of 5 including: (1) Slope of Slope; (2) Rainfall; (3) Soil type; (4) rock types; (5) Land use; The analytical method used is in the form of analysis of basic physical conditions, with this method used to analyze data by describing the state of the natural physical conditions in the research area. The analytical method used is in the form of qualitative descriptive analysis, with this method used to analyze how the proposed land use control of landslide prone areas is made based on the typology of the prone zones according to the level of vulnerability. The analytical method used is in the form of superimpose analysis, with this method used to determine landslide-prone areas. The results of the analysis show that the level of landslide hazard in Samaenre Bi Village is divided into 3, namely: High hazard level with an area of ​​25.79 Ha or 24.82% Medium hazard level with an area of ​​16.85 Ha or 15.21% and Low hazard level with an area of ​​61.28% Ha or 58.97% . Furthermore, disaster mitigation efforts in residential areas prone to landslides in Samaenre Village can be carried out by means of pre-disaster mitigation efforts in residential areas, mitigation efforts in the event of a disaster in residential areas prone to landslides, and post-disaster mitigation efforts in residential areas prone to landslides. . The results of this study are expected to facilitate decision making in policy analysis for landslide-prone areas based on disaster mitigation in residential areas.